Profil Guru Pendidikan Agama Kristen sebagai Pemimpin yang Melayai - Arozatulo Telaumbanua (JURNAL TERUNA BHAKTI, 2020)
The task of Christian religion teachers is not just teaching but also leaders of their students. The task of the Christian religion teacher is complex so as to enable his leadership to focus more on the concept of service that brings students more disciplined and quality. The Christian teacher as a leader who serves is to give his time, energy, thoughts, and life as an educator. Qualified Christian religion teachers are able to lead their students with exemplary leadership and love. Serving leadership, Christian religious teachers attach great importance to teaching that leads students to better understand the meaning of their lives as Christians. The concept of Christian religious teacher leadership is intended to focus more on the leadership of student characters. Character leadership is the goal of Christian religious education to produce great leaders and characters like the Lord Jesus Christ. In this study, the authors use library research methods, namely books and literature as a source of data. Abstrak Tugas guru agama Kristen tidak hanya sekadar mengajar tetapi juga pemimpin bagi muridnya. Tugas guru agama Kristen adalah kompleks sehingga memungkinkan kepemimpinannya lebih fokus pada konsep pelayanan yang membawa muridnya lebih disiplin dan berkualitas. Guru agama Kristen sebagai pemimpin yang melayani adalah memberikan waktu, tenaga, pikiran dan kehidupannya sebagai pendidik. Guru agama Kristen yang berkualitas mampu memimpin muridnya dengan kepemimpinan teladan dan kasih. Kepemimpinan yang melayani, guru agama Kristen mementingkan pengajaran yang membawa murid lebih memahami makna hidupnya sebagai orang Kristen. Konsep kepemimpinan guru agama Kristen yang dimaksudkan lebih fokus pada kepemimpinan karakter murid. Kepemimpinan karakter merupakan tujuan pendidikan agama Kristen untuk menghasilkan pemimpin yang hebat dan berkarakter seperti Tuhan Yesus Kristus. Di dalam penelitian ini penulis menggunakan metode penelitian pustaka, yakni buku dan literatur sebagai sumber data.